The role of women in agricultural associations as a pillar of social developmentin the southern provinces of Santander (case study) - Corzo Gutiérrez, Nohora; Fajardo-Rojas, Miguel Arturo; Sarmiento Blanco, Uriel (Cooperativismo & Desarrollo, 2025)
This article explores the role of women in agricultural associations in the southern provinces of Santander, reflected in their daily work, strong leadership, empowerment, management, and in the various processes that enrich and strengthen the solidarity economy sector. The aim is to improve their living conditions and those of their communities by fostering social development in a collective and participatory manner. A non-experimental descriptive mixed-method approach was used; the technique employed was the interview, and the instrument was a questionnaire directed at rural women-led agricultural associations. Among the findings, it was noted that women carry out tasks both at home and within the associations to which they belong. Their empowerment and leadership are closely tied to the perceived needs of their communities. The family unit practices the principles of solidarity, and the motivation of children and youth lies in the opportunity to actively participate in these associations and the work they carry out, raising awareness of their natural wealth.